Structural Optimization of H-Type Press Table Design Parameters Using Taguchi Method and Finite Element Analysis - Eko wahyu Saputra (Jurnal ELEMENTER (Elektro dan Mesin Terapan), 2026)
This study aims to analyse the influence of load variation, material type, and thickness on the Von Mises stress values of an H-type press table using Design of Experiments (DOE) based simulation approach. This study was conducted to determine the maximum strength of the press machine table design as an effort to prevent structural failure during the operation of the press machine. The “Smaller is Better” signal-to-noise (S/N) ratio criterion was applied to obtain the minimum stress value under loading conditions. Lower stress values indicate a safer load distribution, which can improve the safety factor of the H-type press machine table design. In this study, three load levels were used: 10, 20, and 30 tonnes; three material types: Mild Steel, High-Strength Steel, and Alloy Steel; and three variations in press table thickness: 30, 40, and 50 mm. The simulation results show that as the applied load increases, the Von Mises stress also increases. Changes in the thickness of the press table have the greatest influence on stability or response variation, while the material type has a relatively small influence compared to the other factors. Changes in thickness affect the Von Mises stress value depending on the material type, and vice versa. This indicates that the three parameters interact, meaning a change in one factor can produce different results depending on other conditions. The highest average stress value was obtained on the press table at 104.45 MPa for the combination of High-Strength Steel with a thickness of 30 mm and a load of 30 tonnes, while the lowest stress value of 21.97 MPa was obtained for Alloy Steel with a thickness of 50 mm and a load of 10 tonnes.